Electrical Analysis of Combination of Orange Peel and Tamarind for Bio-battery Application as an Alternative Energy - Anshar, Aghisna Nuthfah; Maulana, Aldi; Nurazizah, Siti; Nurjihan, Zalfa; Anggraeni, Sri; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2021)
The use of disposable primary batteries causes environmental pollution due to the lack of battery waste treatment facilities, so it is necessary to handle the problem by making bio-batteries from orange peel and tamarind. The purpose of this study is to know the influence of good electricity on variations of the combination of orange peel and tamarind. The novelty of this study is (1) the use of biomass combination of orange peel and tamarind as bio-battery electrolytes and (2) comparison of orange peel to tamarind. The method used in this study is by experimenting with a mixture of sweet orange peel and tamarind made into pasta and put in a used battery. The results showed that bio-batteries with a variation of 25% orange to tamarind had the highest voltage and the most powerful electric current. This happens because the ion content in the variation is not concentrated so it is easy to move widely. In conclusion, bio-batteries with a mixture of orange peel and acid are the best variation of 25% orange peel against tamarind. The study is expected to reduce the use of chemicals in batteries and reduce disposable battery waste.